Age-related variations in trunk muscle activation and kinematics during lifting in chronic low back pain: a cross-sectional study - Tianwei Zhang; Ali Firouzabadi; Daishui Yang; Sihai Liu; Lukas Mödl; Hendrik Schmidt (Scientific Reports, 2025)
Abstract Chronic low back pain (cLBP) is a leading cause of disability worldwide, however, the influence of age on electromyography (EMG) during lifting tasks is not well understood. This study examined the effects of age and pain on EMG and kinematics in 102 participants. They were divided into no low back pain (no-BP) (n = 42; mean age: 41.86) and cLBP groups (n = 60; mean age: 43.41) and further categorized by age: 44 under 40 years (mean age: 31.14) and 58 over 40 years (mean age: 51.38). Two lifting tasks from the ground to the hip height were performed: lifting a 10 kg box in front of the body (Task 1) and two 5 kg dumbbells beside the body (Task 2), with EMG and flexion angles recorded. Older participants showed significantly higher EMG amplitudes (p < 0.05), particularly in Task 1 while holding the weight at hip height. No significant EMG differences were found between cLBP and no-BP groups after adjusting for age, sex, and body mass index (BMI) (p > 0.05). Task 1 showed higher back muscle activation than Task 2 (p < 0.05). These findings suggest that age, rather than pain, may play a more critical role in muscle activation, highlighting the need for age-specific interventions in cLBP rehabilitation.